Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
m=-3
x1,y1=1,-5
we have,
y-y1=m(x-x1)
y-(-5)=-3(x-1)
y+5=-3x+3
3x+y+2=0 is the required eqn
Answer:
y = -5
x = 1
m = -3
Step-by-step explanation:
hopefully this makes more sense <3
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.